2021
DOI: 10.1177/15500594211035923
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of EEG in Patients With COVID-19: EEG Recording in Acute and Follow-up Phases

Abstract: Background. Interest in electroencephalographic (EEG) coronavirus disease 2019 (COVID-19) findings has been growing, especially in the search for a specific-features EEG of encephalopathy. Methods. We made a retrospective analysis of 29 EEGs recorded in 15 patients with COVID-19 and neurological symptoms. We classified the EEGs as “Acute EEG” and “follow-up EEG.” We did a statistical analysis between voltage and respiratory status of the patient, stay or not in the intensive care unit (ICU), days of stay in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…Higher prevalence of attenuated patterns was reported in two more recent studies, reaching 21-25% of cases [16,19]. The association between generalized attenuation and higher mortality was postulated but not confirmed [16]. In patients who performed more than one EEG, we observed that the attenuation pattern found in the latter EEG was more likely to predict unfavourable outcome.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Higher prevalence of attenuated patterns was reported in two more recent studies, reaching 21-25% of cases [16,19]. The association between generalized attenuation and higher mortality was postulated but not confirmed [16]. In patients who performed more than one EEG, we observed that the attenuation pattern found in the latter EEG was more likely to predict unfavourable outcome.…”
Section: Discussioncontrasting
confidence: 65%
“…Diffuse attenuation has also been reported in other case series, but almost always in small percentages [2,7,18] or presumably none [13,14]. Higher prevalence of attenuated patterns was reported in two more recent studies, reaching 21-25% of cases [16,19]. The association between generalized attenuation and higher mortality was postulated but not confirmed [16].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…According to a systematic review and meta-analysis, the proportion of abnormal EEG in C19 subjects is as high as 96% 16 . Non-specific, generalized background or diffuse slowing has been reported in several studies as the most common finding 10 , 11 , 18 , whereby EEG abnormalities correlate with encephalopathy, disease severity 8 , 9 , 17 , and risk for novel seizures 13 , including psychogenic non-epileptic seizures 5 . In particular, delta waves with absence of epileptic activity have been documented 12 , as well as alpha coma patterns suggestive of SARS-CoV-2 neurotropism for the brainstem ascending reticular system 15 .…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective chart review of 42 SARS-CoV2-infected patients found 9 (21.4%) had EEGs with an encephalopathy pattern, defined as continuous or rhythmic frontal or diffuse slow diphasic or triphasic waves or sharp waves ( 14 ). In a study by Saez-Landete et al, common EEG characteristics of nonspecific diffuse slowing and low voltage EEG were identified on acute and follow-up EEGs on 15 SARS-CoV2 infected patients ( 15 ). Although there have been several studies characterizing encephalopathy and related conditions, there are still gaps in the literature predominantly due to the heterogeneity of small studies whose methods vary widely.…”
Section: Introductionmentioning
confidence: 99%